Identifying Chinese supply shocks: Effects of trade on labor markets - Andreas M. Fischer; Philipp Herkenhoff; Philip Sauré (Review of International Economics, 2023)
An influential literature estimates the impact of trade on labor markets with shift-share instrumental variable designs under the assumption that common demand shocks in advanced economies are negligible. This article documents empirical patterns, which suggest that such common demand shocks are prevalent. It then proposes a strategy that directly identifies country-specific export supply shocks. Finally, it uses these supply shocks in reduced-form regression, which suggest contractions of manufacturing employment that are larger than those in the seminal contribution by Autor et al. (American Economic Review, 2013, 103, 2121–2168).
Keywords: 330; employment; instrumental variable; international trade